Analisis Keterampilan Menulis dalam Pembelajaran Bahasa Indonesia Siswa Kelas IV SD Negeri Gondrong 2 Kota Tangerang - Ahmad Iklil Asfari; Yeni Nuraeni; Yenni Yenni (AS-SABIQUN, 2022)
This study was to determine the abilities and difficulties in writing skills experienced by fourth grade students of SD Negeri Gondrong 2 Tangerang City. This study uses a descriptive type of research through a qualitative approach that uses the instruments of observation, tests, and interviews. Researchers managed to collect 28 writings from the questions that the researchers gave. From the results of student writing that has been analyzed by researchers, the results obtained in the form of writing skills for fourth grade students at SDN Gondrong 2 Tangerang City are sufficient. Average details on each aspect in the use of capital letters with an average of 2 (enough), the use of punctuation marks with an average of 2 (enough), word selection with an average of 2 (enough), effective sentences with an average of 2 (enough), and paragraphs with an average of 3 (good). Of the five aspects, if put together, the result is 2 (enough). The results of this study can be concluded that, the writing skills of fourth grade students in learning Indonesian with sufficient scores have problems and difficulties in finding ideas, compiling words, confused to start, forgetting the material rules in writing skills.